Trade reforms and firm value: Worldwide evidence - Kong, Linghua; To, Thomas; Wu, Eliza (Journal of Financial Stability, 2026)
Tariffs are commonly used to protect domestic firms from foreign competition. Using 25 major trade reforms implemented in 17 countries around the world since 1990, we document that firm value significantly increases following reductions in import tariffs. This value enhancement is concentrated in emerging markets and countries with stronger ex-ante competition laws. We identify two channels driving the increase in firm value: an increase in firm efficiency and profit margins due to lower input costs, and an increase in CEO turnover-performance and pay-performance sensitivity driven by increased competition. Overall, our findings underscore the importance of trade liberalization, while also highlighting the critical role of institutional support in fostering competition from foreign firms to stimulate private sector growth. • Firm value rises significantly after major tariff reductions worldwide. • Reduced input costs and improved managerial incentives drive value enhancement. • Effects are amplified in small, manufacturing, and import-dependent firms • Effects are concentrated in emerging markets and countries with competitive legal frameworks. • Trade reforms increase firm investment, product development, and operating efficiency